The status quo before the International Standard for Education: Elite adolescent athletes' perceptions of anti-doping education. Issue 3 (October 2021) - Gatterer, Katharina; Streicher, Bernhard; Petróczi, Andrea; Overbye, Marie; Schobersberger, Wolfgang; Gumpenberger, Matthias; Weber, Kathrin; Königstein, Karsten; Blank, Cornelia
ABSTRACT: Education is a fundamental pillar of anti-doping. With the International Standard for Education (ISE) coming into effect in 2021, understanding the status quo of anti-doping education is paramount. This study aimed to evaluate young elite athletes' perceptions of the anti-doping education they receive. A total of 2, 232 athletes, participating at any of four Youth Olympic events between 2018 and 2020 (representing 49 sport disciplines and 124 countries) were surveyed using an online questionnaire, including questions about the anti-doping education received, athletes' views about its usefulness and trust in its content. Additionally, anti-doping education programmes of the countries' National Anti-Doping Organisations (NADOs) were assessed in terms of scope and extent, and categorised as 'comprehensive', 'selective', 'limited' or 'information-only'. Perceived usefulness and trust were compared between these groups. Three-quarters (73.3%) of the athletes received anti-doping education, its usefulness and trust were rated as 'good' (> 4 out of 5). Based on NADO's anti-doping education, athletes in the 'information-only' category had significantly lower values for usefulness and trust, while those in the 'selective' category had the highest values. Results confirm the importance of a multifaceted education, recommending the implementation of at least one educational approach above information provision as they were perceived to be more useful and trusted, and could facilitate Code compliance via developing skills as well as knowledge for informed decision making.